Exhaled nitric oxide measurement before pediatric adenotonsillectomy: A feasibility study. Issue 9 (25th June 2020) - Jablonka, Denis H.; Nishisaki, Akira; Feldman, Jeffrey M.; Galvez, Jorge A.; Gurnaney, Harshad G.; Rizzi, Mark D.; Simpao, Allan F.; Subramanyam, Rajeev; Litman, Ronald S.
Abstract: Background: Exhaled nitric oxide (eNO) is a known biomarker for the diagnosis and monitoring of bronchial hyperreactivity in adults and children. Aims: To investigate the potential role of eNO measurement for predicting perioperative respiratory adverse events in children, we sought to determine its feasibility and acceptability before adenotonsillectomy. Methods: We attempted eNO testing in children, 4‐12 years of age, immediately prior to admission for outpatient adenotonsillectomy. We used correlations between eNO levels and postoperative adverse respiratory events to make sample size predictions for future studies that address the predictability of the device. Results: One hundred and three (53%) of 192 children were able to provide an eNO sample. The success rate increased with age from 23% (9%‐38%) at age 4 to over 85% (54%‐98%) after age 9. Using the eNO normal value (<20 ppb) as a cutoff, an expected sample size to detect a significant difference between children with and without adverse events is 868, assuming that respiratory adverse events occur in 29% of children. Conclusions: eNO testing on the day of surgery has limited feasibility in children younger than 7 years of age. The most common reason for failure was inadequate physical performance while interacting with the testing device. The role of this respiratory biomarker in the context of perioperative outcomes for pediatric adenotonsillectomy remains unknown and should be further studied with improved technologies.